Sentiment Analysis of Digital Nomad in Indonesia: A Case Study in Bali - Rahayu, Dewi Puspita; Kusumastuti, Ayu; Puspitosari, Wida Ayu (UI Scholars Hub, 2021)
The digital nomad is a new type of worker who works from a location other than a “traditional office,” with the freedom to choose where and when to work as long as they have good internet access. The presence of digital nomads has an impact on the dynamics or social changes in society. The public’s reaction to the appearance of this digital traveler was mixed. Some people believe that these new ways of working will harm the work system, but many are gradually adopt it. Bali has become one of the strategic locations and is widely used as a destination for digital nomads. In fact, this is supported by the work from Bali policy which aims to drive the economy in Bali, especially during the pandemic. Indonesia, on the other hand, does not yet have any specific regulations governing digital nomads. The goal of this research is twofold: the first is to conduct a sentiment analysis on Twitter about digital nomads to see how the community reacts, and the second is to see the implications of government policies regarding digital nomads. This study employs qualitative methods with a case study approach, as well as big data methods related to sentiment analysis.